Observations of copper deposition on functionalized carbon nanotube films. (1st April 2017) - Hannula, Pyry-Mikko; Aromaa, Jari; Wilson, Benjamin P.; Janas, Dawid; Koziol, Krzysztof; Forsén, Olof; Lundström, Mari
Abstract: This research details the spontaneous electroless and electrodeposition of copper onto carbon nanotube (CNT) film from a copper sulfate electrolyte. Inhomogeneous electrodeposition was found to occur on pristine CNT film due to differences in available active nucleation sites and the hydrophobic nature of the film. In order to improve the electrochemical response of CNT films, oxidative pre-treatments such as heat treatment and anodization were investigated. These treatments were shown to increase the amount of oxygen containing defects at the surface of CNT film material. Incorporation of functional groups were shown to enhance the wetting of the aqueous electrolyte and created a highly active surface suitable for homogenous electrodeposit. Cathodic polarization curves showed that the presence of functional groups decreased the required level of polarization for copper deposition. Nevertheless, after a certain level of functionalization the polarization starts to decrease due to increased resistivity of the CNT film. Oxygen grafted CNT films were also shown to exhibit enhanced adsorption and reduction of copper without applied voltage due to redox replacement reactions, which were observed to increase with enhanced levels of functionalization.